Asymptomatic Bacteriuria and Antibiogram of Isolates Among Diabetic Patients in Calabar, Nigeria - Paul Inyang-Etoh; Etefia Etefia; Sonia Ejiofor (Universitas Nahdlatul Ulama Surabaya, 2023)
Asymptomatic bacteriuria is the presence of bacteria in the urine of an individual without any symptom of urinary tract infection. This has been widely observed in diabetic patients and could be detrimental to their health if not effectively managed. This study was to identify the pathogens associated with asymptomatic bacteriuria among patients with diabetes and the antibiogram of those isolates in Calabar. Blood samples were collected for the determination of fasting blood sugar levels using glucometer. Bacterial isolations were done through urine culture and antibiogram were tested in all urine samples of the diabetic patients in this study. The prevalence of bacteriuria in this study was 26.0%. Participants aged, 41-50 years were highest both in blood sugar level (12.3+/-4.38mmol/L) and infection rate (37.5%, 18/48). Females had lower blood sugar (10.9+/-3.370mmol/L) than the males (11.3+/-4.46mmol/L) while the males had less infection rate (22.4%, 22/98) than the females (29.4%, 30/102). Escherichia coli, 46.2% (24/52) had the highest distribution while Proteus spp. 11.5% (6/52) had the least distribution. Ciprofloxacin was the most sensitivity (100%) while Amoxicillin was the most resistant (38%). There was a high prevalence of asymptomatic bacteriuria in this study. The most commonly observed organisms were Escherichia coli. Ciprofloxacin was the most sensitive antibiotics and there was a widespread antibiotic resistance in this study. It is therefore recommended that screening among diabetic patients for urinary tract infections, sensitization and strategies to promote effective drug usage be encouraged.